EFFICIENCY OF MANAGEMENT COMPETENCIES OF DIRECTORS DURING THE COVID-19 PANDEMIC (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: At global and national level, the COVID-19 pandemic is influencing the public to increasingly speak of and recognize the importance of preserving the healthcare system. In addition to the solutions found in the formation of new healthcare policies, legal regulations, the role of the director is increasingly recognized, which is important for achieving goals and success as well as for preserving the healthcare system.Methodology: The study involved 27 respondents, i.e. directors of healthcare institutions at the primary level in the Republic of Croatia. All collected data were processed using the IBM SPSS Statistics statistical software.Results: Research results and the theoretical framework of the paper will present the factors influencing the management process of directors in the health system and the importance of the need to revise legislation and the education system aimed at ensuring the sustainability of public health.Conclusion: The paper will present which competencies of directors of healthcare institutions are crucial for crisis management during the COVID-19 pandemic.